Statistical analysis of abnormal phase shift quiet days (APQDS) in low-/mid-latitudes for solar cycle 24 (2008–2019) - Ali, Muneeza (https://orcid.org/0009-0006-2646-6070) (Rhodes University, 2026)
The solar quiet (Sq) focus position of normal quiet current systems is usually around ± 30◦from the magnetic equator. Deformed Sq current vortices observed away from this position may contribute to abnormal phase-shift quiet days (APQDs). Moreover, regional variations, hemispheric asymmetries of neutral winds, conductivities, and non-migrating tides may influence the APQDs. To understand this phenomenon, a statistical analysis of APQDs was conducted for Solar Cycle 24 (SC24: 2008-2019). The study used 1-min magnetic field data from 43 INTERMAGNET geomagnetic observatories between −60◦ and +60◦ magnetic latitudes in three longitudinal sectors: American, Africa-European, and Asia-Australian. Quiet days were identified by a |SYM-H| ≤ 10nT threshold. APQDs were identified in low- and mid-latitudes to shed light on regional, global, and seasonal occurrence rates. Results showed high global and regional APQD occurrences during D season across solar cycle phases in all longitudinal sectors. Moreover, the highest occurrence rate of regional and global APQDs was observed in the Northern Hemisphere’s low-latitudes (43.4% & 36.7%) and in the Southern Hemisphere’s mid-latitudes (31% and 31.4%), respectively. For hourly distribution of APQDs occurrence rates, mostly in the D season, high rates were observed in the morning (6:30-9:30 SLT) for low latitudes in the Northern Hemisphere and in the afternoon (15:30-16:30 SLT) for mid-latitudes in the Southern Hemisphere. The results showed that the sudden stratospheric warming (SSW) event might have influenced the ionospheric current system on 23 January 2009, most likely shifting Sq foci latitudes to 55◦N and 54◦S, and causing APQDs at mid-latitude observatories and equatorial observatory MBO.
Keywords: Geomagnetism -- Observations (http://id.loc.gov/authorities/subjects/sh85079766); Solar cycle (http://id.loc.gov/authorities/subjects/sh85124499); Physics; Sq-Variation (https://www.wikidata.org/wiki/Q2314949)